1986
DOI: 10.2466/pr0.1986.58.1.327
|View full text |Cite
|
Sign up to set email alerts
|

Child Molestation and Homosexuality

Abstract: How much child molestation occurs in our society and how much is homosexual? Random-probability samples in Los Angeles, Denver, Omaha, Louisville, and Washington, DC yielded 4,340 adults who answered an extensive questionnaire regarding sexual attitudes, activities, and experiences. Results indicate that perhaps 16% of both boys and girls claim sexual relations with an adult before the age of 16; if only experiences with men are counted about 5% of boys and 15% of girls claim sexual involvements. Sexual contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…The same erroneous assumption is the basis for a paper published by the same author, provocatively titled "Child Molestation and Homosexuality" (Cameron et al, 1986). Drawing data from a door-to-door survey in seven U.S. cities and towns, Cameron refers to male-male sexual assaults as "homosexual" molestations (e.g., Abstract, p.327), despite his lack of data about the sexual orientation of perpetrators.…”
Section: Stereotypes and Cultural Ideologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The same erroneous assumption is the basis for a paper published by the same author, provocatively titled "Child Molestation and Homosexuality" (Cameron et al, 1986). Drawing data from a door-to-door survey in seven U.S. cities and towns, Cameron refers to male-male sexual assaults as "homosexual" molestations (e.g., Abstract, p.327), despite his lack of data about the sexual orientation of perpetrators.…”
Section: Stereotypes and Cultural Ideologiesmentioning
confidence: 99%
“…In his written opinion in Baker v. Wade (1985), Judge Buchmeyer of the U.S. District Court of Dallas referred to "Cameron's sworn statement that 'homosexuals abuse children at a proportionately greater incident than do heterosexuals,'" and concluded that "Dr. Paul Cameron...has himself made misrepresentations to this Court" and that "There has been no fraud or misrepresentations except by Dr. Cameron" (p.536). 10 Brown and Cole (1985) criticized the sampling methods of Cameron et al (1985Cameron et al ( , 1986 Oberman (1984), for example, quoted a 16th century German account of how a group of Jews "purchased seven Christian children" whom they subsequently "pierced with needles and knives, tortured, and finally killed," and then "prepared the blood with pomegranates and served it for dinner" (p. 99). As noted by Adam (1978), lynchings of American Blacks were traditionally justified with the contention that "many Negroes were literally wild beasts with uncontrollable sexual passions" (p.45); Black males were portrayed as a threat to White women.…”
Section: Stereotypes and Cultural Ideologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…161 Using the results of the survey, Cameron published a series of articles arguing that gays and lesbians were more likely to molest children and commit incest. 162 His work identified child sexual abuse as the cause of homosexuality, and since he maintained that gay and lesbian parents were more likely to have homosexual children, he concluded that gay parents were likely to molest their children. 163 Although all of Cameron's articles were fervently anti-gay, his 1986 article entitled "Child Molestation and Homosexuality" also included a media study that concluded that the media over-reported homosexual molestation.…”
Section: A Anti-gay and Lesbian Parenting Researchmentioning
confidence: 99%
“…The self-administered questionnaire included 550 questions and required an estimated seventy-five minutes to complete. 159 Cameron distributed the survey to over 10,000 adults in six United States cities, with almost half returning the completed questionnaire. 160 The survey included questions about sexual experiences, sexual object choice, and family structure growing up.…”
Section: A Anti-gay and Lesbian Parenting Researchmentioning
confidence: 99%